2014
DOI: 10.1063/1.4870512
|View full text |Cite
|
Sign up to set email alerts
|

Current-voltage spectroscopy of dopant-induced quantum-dots in heavily n-doped junctionless nanowire transistors

Abstract: We demonstrate current-voltage spectroscopy of dopant-induced quantum dots in heavily n-doped junctionless nanowire transistors (JNTs) at low temperatures. The similar multiple-split current peak features for both single-channel and multiple-channel JNTs are found at the initial stage of conduction below the temperature of 75 K. The temperature stability of the pinch-off voltage, affected by activated electrons from defects and donor ionization, has been effectively improved by the 20 nm-width nanowires. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the blinding energy of the dopants is largely enhanced by the confined environment. [27][28][29] In JNT, the initial conduction path is ultra-narrow, forming enhanced blinding effect. As a consequence, the dopant blinding energy and the charging energy are both enhanced through quantum confinement and dielectric confinement.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the blinding energy of the dopants is largely enhanced by the confined environment. [27][28][29] In JNT, the initial conduction path is ultra-narrow, forming enhanced blinding effect. As a consequence, the dopant blinding energy and the charging energy are both enhanced through quantum confinement and dielectric confinement.…”
Section: Resultsmentioning
confidence: 99%
“…The onset gate voltage V gt increases from 6 K to 20 K and decreases from 100 K to 250 K, resulting from the interaction of the induced image charges in the dielectric interface with the impurity and the subband states in the channel. [13] To explore the conductance characteristics under the same filled energy level, we take the onset gate voltage V gt to unify the transfer characteristics in Fig. 2(a) for the alignment of energy levels at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] As the channel width of the silicon transistor is scaled down to several nanometers, few ionized dopant atoms randomly distributed in the channel can work as quantum dots (QDs) and play a significant role in the electron transport behaviors. [10][11][12][13][14] In recent years, singleelectron tunneling through the dopant-induced QD array has attracted much attention in the study of the silicon junctionless nanowire transistors (JNTs), which may provide a onedimensional bulk channel with an adjustable width by the gate electric field. [7,15,16] The conducting path in the center of the silicon nanowire, which is effectively confined by the surface depletion potentials, can be gradually broadened to the whole conduction channel region with the increase of the gate voltage.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the current-voltage spectroscopies of dopant-induced quantum dots in single-channel and multiplechannel n-doped junctionless nanowire transistors (JNTs) [42,43] . There is nearly the identical size of dopant-induced QDs and the similar inter-QD coupling effect in single-channel and multiple-channel JNTs.…”
Section: Coupling Of Dopant-induced Quantum Dotsmentioning
confidence: 99%